De novo variants in SUPT16H cause neurodevelopmental disorders associated with corpus callosum abnormalities. Issue 7 (10th January 2020) - Bina, Roya; Matalon, Dena; Fregeau, Brieana; Tarsitano, Jacqueline Joani; Aukrust, Ingvild; Houge, Gunnar; Bend, Renee; Warren, Hannah; Stevenson, Roger E; Stuurman, Kyra Eva; Barkovich, A James; Sherr, Elliott H.
Abstract : Introduction: Whole-exome sequencing (WES) has identified de novo variants in chromatin remodelling genes in patients with neurodevelopmental disorders (NDD). We report on a novel genetic discovery in chromatin remodelling in patients with NDD who also have corpus callosum (CC) anomalies. Objective: To discover novel genes linked to both CC anomalies and NDD. Methods: Clinical WES was performed for evaluation of NDD, identifying five patients with de novo variants in SUPT16H, a subunit of the FACT (facilitates chromatin transcription) complex. The clinical phenotypes, genetic results and brain MRIs were obtained and systematically reviewed. In silico protein function predictions were assessed and allele frequencies in control populations were compared. Results: We identified four patients with de novo missense variants in SUPT16H and one patient with a de novo deletion including SUPT16H . These variants were not reported in the updated Genome Aggregation Database. When assayable, all protein products were predicted to be damaging. Symptoms included intellectual disability, autistic features, minor dysmorphic features and seizures. Anomalies of the CC were seen in all three patients with available brain imaging. Conclusion: Our findings implicate the gene SUPT16H in a novel disorder characterised by neurodevelopmental deficits and CC anomalies.